1985
DOI: 10.1073/pnas.82.19.6384
|View full text |Cite
|
Sign up to set email alerts
|

The "beta-like-globin" gene domain in human erythroid cells.

Abstract: We have mapped the distribution of the major and minor DNase I-hypersensitive sites in the human "fi-like-globin" gene domain. The minor DNase I-hypersensitive sites map close to the 5' end of each of the 13-like-globin genes. Their presence is specifically associated with the transcription of the immediate downstream fi-like-globin genes.The major DNase I-hypersensitive sites map in what appear to be the 5' and 3' boundary areas of the human fi-like-globin gene domain, a region estimated to span at least 90 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
356
2
10

Year Published

1990
1990
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 608 publications
(376 citation statements)
references
References 25 publications
8
356
2
10
Order By: Relevance
“…[10][11][12][13] The regulation of HbF level might be a complex genetic trait governed by genetic elements linked to the b-globin gene-like cluster and quantitative trait loci (QTL) present on chromosomes 6, 8 and on the X-chromosome; other regulatory loci are also likely to exist and epigenetic and cellular factors could also have regulatory roles. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] It is possible that these and other regulatory elements also modulate the HbF response to HU. Accordingly, we hypothesized that single nucleotide polymorphisms (SNPs) in candidate genes or QTL with putative roles in the regulation of HbF production might modulate the HbF response to treatment with HU.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] The regulation of HbF level might be a complex genetic trait governed by genetic elements linked to the b-globin gene-like cluster and quantitative trait loci (QTL) present on chromosomes 6, 8 and on the X-chromosome; other regulatory loci are also likely to exist and epigenetic and cellular factors could also have regulatory roles. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] It is possible that these and other regulatory elements also modulate the HbF response to HU. Accordingly, we hypothesized that single nucleotide polymorphisms (SNPs) in candidate genes or QTL with putative roles in the regulation of HbF production might modulate the HbF response to treatment with HU.…”
Section: Introductionmentioning
confidence: 99%
“…The b-globin locus control region (LCR), which plays an essential role in this regulation (Grosveld et al, 1987), is divided into four distinct 200 ± 300 bp core regions (HS-1, HS-2, HS-3 and HS-4) all showing DNase I hypersensitivity (Grosveld et al, 1987;Tuan, 1985). Three types of DNA binding sites, i.e., GATA, Sp1 and NF-E2-like motifs, are found within the core sequences Talbot et al, 1990;Talbot and Grosveld, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The LCR is characterized by the presence of four erythroid-specific, developmentally stable DNaseI hypersensitive sites [9]. We and others have previously shown that the activity of the LCR resides in these hypersensitive site (HS) regions and identified the core elements as 200-300 bp fragments [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%